Bridging the gap: a researcher’s journey from traditional qualitative methods to tech-driven insights - Lee, Khuan; Jamil, Nurul Akma; Abdul Rashid, Nor'ain; Muda, Siti Mariam (SOTVI - Society of Visual Informatics, 2024)
The integration of technology into qualitative research has introduced transformative opportunities and challenges, prompting researchers to evaluate traditional methods against technology-based approaches. This article examines the strengths, limitations,and effectiveness of these methods, focusing on participant recruitment, interview conduction, and transcription processes. Drawing on researchers’ experiences from two qualitative projects involving breastfeeding mothers, this article compares traditional face-to-face interviews with online methods using platforms such as Zoom and Facebook. The findings reveal that while face-to-face interviews enable deeper interaction and contextual insights, they are logistically demanding and time-intensive. In contrast, technology-based methods enhance accessibility and efficiency, particularly for dispersed populations, yet may compromise non-verbal cues and transcription accuracy. Automated transcription tools, though time-saving, often fail to capture linguistic nuances, requiring manual verification for rigorous analysis. This article concludes that a hybrid approach leveraging the strengths of both methods ensures comprehensive data collection. Best practices for using technology in qualitative research are proposed to ensure the richness and contextual depth of the data while leveraging the benefits of modern tools.